2017
DOI: 10.1007/s00018-017-2578-x
|View full text |Cite
|
Sign up to set email alerts
|

How Schwann cells facilitate cancer progression in nerves

Abstract: Recent studies have demonstrated a critical role for nerves in enabling tumor progression. The association of nerves with cancer cells is well established for a variety of malignant tumors, including pancreatic, prostate and the head and neck cancers. This association is often correlated with poor prognosis. A strong partnership between cancer cells and nerve cells leads to both cancer progression and expansion of the nerve network. This relationship is supported by molecular pathways related to nerve growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 149 publications
(218 reference statements)
3
100
0
Order By: Relevance
“…While the number of investigations into the neuronal regulation of cancer has increased in recent years, the involvement of the peripheral neuroglia in cancer progression remains poorly understood (11,12). Schwann cells (SC) comprise the majority of the neuroglia of the PNS and are intimately associated with the nerve fibers, providing trophic support and a signaling scaffold for the axon (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…While the number of investigations into the neuronal regulation of cancer has increased in recent years, the involvement of the peripheral neuroglia in cancer progression remains poorly understood (11,12). Schwann cells (SC) comprise the majority of the neuroglia of the PNS and are intimately associated with the nerve fibers, providing trophic support and a signaling scaffold for the axon (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…23 So, some scholars speculated that Schwann-like cell differentiation of tumor cells might be one of the mechanisms of PNI occurrence in tumors. 24,25 In the SACC specimens, Shan et al 17 found that the expression of S100A4 and GFAP around the nerve was distinctly enhanced. However, the relationship between MIF and Schwann-like cell differentiation of tumor cells in PNI of SACC remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The plastic potential of SCs is a double-edged sword. While essential for nerve repair, recent studies point out its adverse effect in neuropathies and epithelial cancer progression (Deborde & Wong, 2017;Horste et al, 2010). Here, we demonstrate a favorable impact of SC plasticity on peripheral neuroblastic tumor cells as it manifests in SC stroma during the development of benignly behaving GNB/GN.…”
Section: Exploiting Schwann Cell Plasticity In Therapeutic Approachesmentioning
confidence: 99%